1991
DOI: 10.1021/ma00002a010
|View full text |Cite
|
Sign up to set email alerts
|

Glass transition and dynamics of phosphate esters dissolved in two glassy polymer matrices

Abstract: Three phosphate ester diluents were added to 5050 blends of polystyrene (PS) with poly-(2,6-dimethyl-1,4-phenylene oxide), also known trivially as poly(xyly1ene ether) (PXE). One of the three diluents was also added to BPA polycarbonate (BPA-PC). The diluents were trioctyl phosphate (TOP), triphenyl phosphate (TPP), and tetraxylyl hydroquinone diphosphate (TXHQDP). The dynamics of these single-phase systems vs temperature were monitored by dynamic mechanical relaxation and phosphorus-31 NMR. Dynamic mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…They mentioned that the reported values in the literature were well above its decomposition temperature. DSC method was not sensitive enough to trace the transitions when there were small changes in heat capacity (Cauley et al, 1991;Quinn et al, 1988). However, the 1 H signal showed high immobility in region 1 (moisture: 0-3 g/100 g dry solids) and even the mobility of the liquid like component was retarded.…”
Section: Water Mobility Conceptmentioning
confidence: 99%
“…They mentioned that the reported values in the literature were well above its decomposition temperature. DSC method was not sensitive enough to trace the transitions when there were small changes in heat capacity (Cauley et al, 1991;Quinn et al, 1988). However, the 1 H signal showed high immobility in region 1 (moisture: 0-3 g/100 g dry solids) and even the mobility of the liquid like component was retarded.…”
Section: Water Mobility Conceptmentioning
confidence: 99%
“…In contrast to the more widely studied plasticizers, antiplasticizers also depress T g , but these additives increase the stiffness (shear or bulk modulus) of polymeric materials in the glass state. [8][9][10][11] This stiffening is of great importance for preservation of biomaterials, such as foods, tissues, and drugs, and for enhancing the scratch resistance of polymer films, controlling the brittleness and other non-linear mechanical properties of polymer materials, etc. Thus, antiplastization has many practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics of low molecular weight molecules dissolved in polymer matrices has been studied long by means of dielectric, 1-8 mechanical, 7,8 NMR, 6,7,9,10 light scattering, 7 fluorescence depolarization, 11 ESR, 12 and thermal methods. 6,13 Adachi et al 4 and Yoshizaki et al 1 reported the dielectric behaviors of the systems consisting of polystyrene (PS) and alkylbenzene such as toluene, ethylbenzene and butylbenzene.…”
mentioning
confidence: 99%